2017
DOI: 10.3389/fimmu.2017.00818
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylatoxin C5a Regulates 6-Sulfo-LacNAc Dendritic Cell Function in Human through Crosstalk with Toll-Like Receptor-Induced CREB Signaling

Abstract: Activation of antigen-presenting dendritic cells (DCs) and the complement system are essential early events in the immune defense against invading pathogens. Recently, we and others demonstrated immunological crosstalk between signaling from receptors recognizing complement activation products and PAMPs on DCs. This affects DC effector function, as demonstrated by the finding that C5a prevents induction of pro-inflammatory cytokines by toll-like receptor (TLR) ligands in human monocyte-derived DCs (moDCs). Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 52 publications
2
16
0
Order By: Relevance
“…However, p38 MAPK inhibition led to an increased production of IL-12p70 that was comparable to that of IL-4/DCs. Our data are in line with the report that showed that C5aR inhibited the pro-inflammatory potential of a very pro-inflammatory human DC subset (slanDCs) and induced IL-10 production by initiating and prolonging ERK and p38 MAPK phosphorylation as well as CREB phosphorylation [67]. Furthermore, inhibition of ERK1/2 or p38 MAPK phosphorylation or inhibition of signal transduction upstream of CREB1 (via MSK1/2 inhibition) abrogated the ability of C5aR to induce IL-10 gene expression in LPS-stimulated moDCs.…”
Section: Discussionsupporting
confidence: 92%
“…However, p38 MAPK inhibition led to an increased production of IL-12p70 that was comparable to that of IL-4/DCs. Our data are in line with the report that showed that C5aR inhibited the pro-inflammatory potential of a very pro-inflammatory human DC subset (slanDCs) and induced IL-10 production by initiating and prolonging ERK and p38 MAPK phosphorylation as well as CREB phosphorylation [67]. Furthermore, inhibition of ERK1/2 or p38 MAPK phosphorylation or inhibition of signal transduction upstream of CREB1 (via MSK1/2 inhibition) abrogated the ability of C5aR to induce IL-10 gene expression in LPS-stimulated moDCs.…”
Section: Discussionsupporting
confidence: 92%
“…To determine whether eTACs represent activated and mature DCs, we compared the transcriptomes of eTACs and cDCs with those of unstimulated and LPS-stimulated monocyte-derived DCs (designated moDC), from Zaal et al (17). After controlling for experimental variation using surrogate variable analysis, we compared these DCs to our tonsil-derived cDCs and eTACs in a reduced dimensional space defined by PCA (Figure 5C).…”
Section: Resultsmentioning
confidence: 99%
“…40 C1q, iC3b, C5a-C5aR, CR1, and factor H are reported to regulate the maturation and function of DCs. 24,25,[55][56][57] CR2 is part of the co-receptor (along with CD19, CD81, and Leu13) of B lymphocytes. 58,59 In the germinal centers, C3 degradation fragment-coated immune complexes are recognized and retained by follicular DCs, enhancing the differentiation of memory and effector B cells.…”
Section: Inter Ac Tion Bet Ween Complement and The Adaptive Immune mentioning
confidence: 99%
“…Antigen‐presenting DCs are critical in adaptive immune defense, and their function is influenced by complement . C1q, iC3b, C5a‐C5aR, CR1, and factor H are reported to regulate the maturation and function of DCs …”
Section: Interaction Between Complement and The Adaptive Immune Systemmentioning
confidence: 99%